Improving the management of warfarin in aged‐care facilities utilising innovative technology: a proof‐of‐concept study. (15th April 2013) - Bereznicki, Luke R. E.; Jackson, Shane L.; Kromdijk, Wiete; Gee, Peter; Fitzmaurice, Kimbra; Bereznicki, Bonnie J.; Peterson, Gregory M.
Abstract Objective In aged‐care facilities (ACFs) monitoring of warfarin can be logistically challenging and International Normalised Ratio (INR control) is often suboptimal. We aimed to determine whether an integrated information and communications technology system and the use of point‐of‐care (POC) monitors by nursing staff could improve the INR control of aged‐care facility residents who take warfarin. Methods Nursing staff identified residents who were prescribed warfarin in participating ACFs. A computer program (MedePOC) was developed to store and transmit INR results from the ACFs to general practitioners (GPs) for dosage adjustment. Nursing staff received training in the use of the CoaguChek XS point‐of‐care INR monitor and the MedePOC software. Following a run‐in phase, eligible patients were monitored weekly for up to 12 weeks. The primary outcome was the change in the time in therapeutic range (TTR) in the intervention phase compared to the TTR in the 12 months preceding the study. All GPs, nursing staff and patients were surveyed for their experiences and opinions of the project. Key findings Twenty‐four patients and 19 GPs completed the trial across six ACFs. The mean TTR for all patients improved non‐significantly from 58.9 to 60.6% (P = 0.79) and the proportion of INR tests in range improved non‐significantly from 57.1 to 64.1% (P = 0.21). The mean TTR improved in 14 patients (58%) and in these patients the mean absolute improvement in TTR was 23.1%. A post hoc analysis of the INR data using modified therapeutic INR ranges to reflect the dosage adjustment practices of GPs suggested that the intervention did lead to improved INR control. The MedePOC program and POC monitoring was well received by nursing staff. Conclusions Weekly POC INR monitoring conducted in ACFs and electronic communication of the results and warfarin doses resulted in non‐significant improvements in INR control in a small cohort of elderly residents. Further research involving modification to the communication strategy and a longer follow‐up period is warranted to investigate whether this strategy can improve INR control and clinical outcomes in this vulnerable population.